1994
DOI: 10.1073/pnas.91.24.11338
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a heritable deficiency of the folate-dependent enzyme 10-formyltetrahydrofolate dehydrogenase in mice.

Abstract: During the analysis of liver protein expression in the offspring of male mice Irradiated with fissionspectrum neutrons, one ofprin displayed a heritable 50% decrease in the abundance of two proteins. Homozygous mice lacing detectable quantities of these proteins were obtained through breeding. Characterization of this protein deficiency has identified these liver proteins as forms of the enzyme 10-formyltetrahydrofolate dehydrogenase (10- Although the physical properties and substrate and product binding chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 20 publications
(15 reference statements)
2
33
0
Order By: Relevance
“…First, Krebs et al (19) suggested that FDH serves to remove excess one-carbon units from folate metabolism by depleting pools of folate-activated one-carbon units. In support of this hypothesis, mice with a heritable FDH deficiency exhibit 4-fold lower relative hepatic THF concentrations and 2.6-fold higher relative 10-formyl-THF concentrations compared with the livers of control mice (16). Second, FDH has been suggested to sequester and store cellular folate in the form of THF (2,20).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…First, Krebs et al (19) suggested that FDH serves to remove excess one-carbon units from folate metabolism by depleting pools of folate-activated one-carbon units. In support of this hypothesis, mice with a heritable FDH deficiency exhibit 4-fold lower relative hepatic THF concentrations and 2.6-fold higher relative 10-formyl-THF concentrations compared with the livers of control mice (16). Second, FDH has been suggested to sequester and store cellular folate in the form of THF (2,20).…”
mentioning
confidence: 95%
“…FDH catalyzes the NADP ϩ -dependent conversion of 10-formyl-THF to THF and CO 2 (1,15). Mice lacking FDH activity are viable and fertile, indicating that one or more FDH functions are not essential in the laboratory environment (16); FDH may function to regulate the folate-medi-* This work was supported by U.S. Public Health Services Grants HD35687 (to P. J. S.) and DK07158-28 (to M. C. A.).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the enzymatic function of FDH, that is the conversion of 10-formyltetrahydrofolate to tetrahydrofolate, was known for decades, the main physiological role of the enzyme is still in question. Proposed FDH functions include regulation of reduced folate pools (Champion et al, 1994), storage of the intracellular folate (Min et al, 1988), regulation of de novo purine biosynthesis (Krupenko and Oleinik, 2002) and regulation of cellular methylation (Anguera et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…ALDH1A3 is expressed in salivary gland, stomach, and kidney (Hsu et al 1994). The ALDH1L1 gene encodes a 10-formyltetrahydrofolate dehydrogenase (Champion et al 1994).…”
Section: Introductionmentioning
confidence: 99%